The Incidental Thyroid Lesion in Parathyroid Disease Management. Issue 1 (March 2017) - Alamoudi, Uthman; Levi, Eric; Rigby, Matthew H.; Taylor, S. Mark; Trites, Jonathan R. B.; Hart, Robert D.
Objective: The incidental thyroid lesion is a common finding during general imaging studies. Their management has been the subject of numerous studies and recommendations. Parathyroid disease workup necessitates imaging investigation of the adjacent thyroid gland and therefore provides a unique window to the perioperative management of thyroid incidentaloma. The specific prevalence of incidental thyroid lesions in the context of parathyroid disease is unknown. We seek to investigate its prevalence during parathyroid workup and surgery and to ascertain if there was a change in management of these patients. Study Design: Five-year retrospective database review. Setting: Tertiary care medical center. Subjects and Methods: The source and indication for referral, preoperative investigation findings, and management of the incidental thyroid lesions were examined. The actual procedure performed and final pathology results were assessed. Results: A total of 98 patients and 106 operations, including revision surgeries, were identified. There were 21 incidental thyroid lesions (21.4%) detected, whereby 15 patients underwent fine-needle aspirations and 12 subsequently had diagnostic hemithyroidectomies. This decision was made preoperatively in 5 patients and intraoperatively in 7 patients at the time of parathyroid surgery. Along with other pathologies, there were 7 patients with micropapillary thyroid carcinoma identified. Conclusions: In our series, the prevalence of incidental thyroid lesion and thyroid malignancy is comparable to the general population. The management of the initial parathyroid disease in our patients was altered by the imaging and cytological findings of these thyroid lesions. This has implications on perioperative counseling of the thyroid and parathyroid disease.